Potential Tourism Village Development Activities in Kerobokan Village, Sawan District, Buleleng Regency, Bali - SAPUTRA, Komang Adi Kurniawan; JAYAWARSA, A.A. Ketut (PT Batara Swastika Harati, 2023)
In order to accelerate Kerobokan Village as a Tourism Village, Warmadewa University held Community Service (PKM). Tourism villages are one of the concepts that develop the potential of an area that can be developed and provide a positive contribution to the community. In building a tourism village, the important thing is a commitment between the government and village officials, community leaders and village organizations to make the village a tourism village. The background of this activity is the need for academics to provide tourism village literacy to the fostered village community. Kerobokan Village has excellent potential to be developed as a Tourism Village. Kerobokan Village has many and stores a variety of cultural heritage wealth that needs to be revived and developed as a tourist attraction to improve the welfare of the people of Kerobokan Village and the surrounding villages